PROTOTIPE FASILITAS PELATIHAN KEWIRAUSAHAAN CENGKEH DI PERKEBUNAN JAMBELAER - Indika Kamara Putra; J.M. Joko Priyono Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Starting from the issues faced by a group of young people from Jambelaer village, Sukabumi, who are seeking work in the city with only junior high school and vocational school diplomas. Some of these youths claim that their fathers were former successful clove entrepreneurs in their village, but went bankrupt due to limited facilities, sales access, and knowledge about clove farming. The farming methods and facilities used by the villagers are still very conventional and highly dependent on weather conditions, resulting in declining harvest yields and selling prices that no longer cover their expenses. Moreover, the farmers lack sufficient knowledge about clove plant care and how to optimize production from clove harvests. As a result, the young farmers have shifted to seeking work in the city, and their clove plantations in the village have been left neglected, as they are considered to have lost their value. This has become a problem because if they are no longer dependent on their natural resources, over time, the importance of clove farming may be forgotten. This project takes the clove plants in their village as the subject of empathy and aims to revitalize clove farming as the main source of income for the village. Therefore, they need a facility for learning and education about clove farming, as well as a processing facility to process their harvests without being too dependent on weather conditions. The proposed architectural solution in this case is a prototype, a building for educational and learning facilities dedicated to everything about clove farming, along with a processing facility. This prototype will be built in the location of the clove plantations owned by the villagers. The "fill in" method will be used, filling in empty areas without significantly cutting down existing clove trees, using locally available building materials from the village to minimize costs and, at the same time, aiming to increase the awareness of the village's youth regarding the richness of their local resources. Keywords: architecture; awareness; clove; empathy; education Abstrak Berangkat dari permasalahan sekelompok anak muda asal kampung Jambelaer, Sukabumi, yang mencari kerja di kota dan hanya berbekal ijazah SMP dan SMK, padahal beberapa anak mengaku ayahnya adalah bekas seorang pengusaha cengkeh yang dulu sukses dikampungnya, tetapi bangkrut karena keterbatasan fasilitas, akses jual dan pengetahuan tentang cengkeh. Metode dan fasilitas yang digunakan para petani kampung tersebut masih sangat konvensional dan sangat tergantung dengan cuaca, akibatnya hasil panen terus menurun dan harga jual sudah tidak menutupi modal mereka. Petani kampung tersebut juga tidak dibekali pengetahuan yang cukup tentang perawatan tanaman cengkeh dan bagaimana mengoptimalkan produksi dari hasil panen cengkeh. Karena hal itu maka para petani beralih mencari kerja ke kota dan kebun cengkeh di kampung mereka dibiarkan terlantar begitu saja karena dianggap sudah tidak memiliki value bagi mereka. Hal ini menjadi masalah karena jika mereka sudah tidak bergantung akan alamnya maka lama kelamaan cengkeh akan dilupakan. Proyek ini menjadikan tanaman cengkeh pada kampung mereka sebagai subjek empati dan mencoba mengangkat kembali tanaman cengkeh sebagai penghasilan utama kampung tersebut. Untuk itu, mereka membutuhkan sebuah fasilitas pembelajaran, pendidikan dan juga pengolahan cengkeh. Solusi arsitektural pada kasus ini merupakan prototype, sebuah bangunan fasilitas pendidikan dan pembelajaran segala hal tentang cengkeh, juga fasilitas pengolahan untuk memproses hasil panen mereka tanpa terlalu tergantung dengan keadaan cuaca. Prototype ini akan dibangun pada lokasi kebun cengkeh warga kampung Jambelaer. Dengan metode fill in, mengisi area kosong tanpa banyak menebang pohon cengkeh yang sudah ada dengan pemakaian material bangunan yang mudah ditemukan pada area kampung mereka untuk meminimalisir biaya dan juga bertujuan untuk meningkatkan kepedulian para pemuda kampung tersebut akan kekayaan sumberdaya kampung mereka.